Canadian History Unsundered: Reflections on Elsbeth Heaman’s Tax, Order, and Good Government - Nielson, Carmen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2019)
I argue that Elsbeth Heaman’s book achieves precisely what Michael Bliss had hoped for when he wrote “Privatizing the Mind: The Sundering of Canadian History, the Sundering of Canada.” This is readable, politically-engaged scholarship that takes seriously Canadian historians’ task of explaining who “we” are, where “we” have been, and where “we” might be going, without mythologizing or homogenizing who that “we” might be.